The Effect of Spirituality on School Well-Being Among Santri - Indra Wijaya; Hasyim Haddade; Ulfiani Rahman; Ahmad Afif (CV. Doki Course and Training, 2026)
This study aims to examine the relationship between spirituality and school well-being among students (santri) in Islamic boarding schools in South Sulawesi. Using a quantitative correlational survey design, data were collected from 416 students selected through multistage cluster random sampling from 12 pesantren. The Spirituality Scale was adapted from the Spiritual Orientation Inventory (SOI) by Elkins et al., while the School Well-Being Scale was adapted from the model of Konu and Rimpelä. Both instruments showed high reliability (α = 0.943 and α = 0.857, respectively). Data were analyzed using Structural Equation Modeling (SEM) with Mplus software. The SEM results indicate that spirituality has a small positive but non-significant direct effect on school well-being (beta = 0.084, p = 0.121). These findings suggest that, in the pesantren context, students’ school well-being may be shaped more strongly by social and structural factors (e.g., peer relationships, social interaction, and institutional policies) than by spirituality alone, highlighting the need for holistic well-being programs.